2015
DOI: 10.4018/ijisp.2015040104
|View full text |Cite
|
Sign up to set email alerts
|

Observations on Genderwise Differences among University Students in Information Security Awareness

Abstract: The purpose of this study is to examine genderwise differences in information security awareness (ISA) among university students. 614 usable responses were collected using survey from the students of eight different disciplines in a university. ISA is considered as combination of knowledge and behavior, and called computed ISA. Knowledge and behavior is assessed using vocabulary test and scenario based questions, whereas perceived ISA (PISA) is measured on 5-point Liker type question. The application of t-test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
3
3
0
Order By: Relevance
“…Male respondents exhibited a risky behaviour for downloading apps from an untrusted third-party repository, connecting to unsecured Wi-Fi networks, updating of apps and rooting or jailbreaking. These results are similar to those obtained by Parker et al (2015) and Farooq et al (2015). Male respondents preferred biometric authentication mechanism, whereas female participants preferred PIN/password.…”
Section: Results and Analysissupporting
confidence: 89%
“…Male respondents exhibited a risky behaviour for downloading apps from an untrusted third-party repository, connecting to unsecured Wi-Fi networks, updating of apps and rooting or jailbreaking. These results are similar to those obtained by Parker et al (2015) and Farooq et al (2015). Male respondents preferred biometric authentication mechanism, whereas female participants preferred PIN/password.…”
Section: Results and Analysissupporting
confidence: 89%
“…In other words, providing academic librarians with more educational training on CDP will increase their awareness on the importance and knowledge of CDP. The findings were consistent with previous studies (Chua et al 2018;Farooq et al 2015;Öğütçü et al 2016) where educational level had a positive influence on the awareness of information security policies. The findings were also consistent with studies conducted in the health profession (Byrd et al 2012;Primomo 2007;Primomo and Björling 2013;Rains and Carroll 2000), where the educational level had a positive relationship with the awareness, knowledge, and possible engagement in health policy development.…”
Section: Discussionsupporting
confidence: 93%
“…This assumption has been supported by several empirical studies that have looked at the awareness and knowledge level of policy in various professions. For instance, in the information profession, educational level was found to be significantly correlated with the awareness and compliance of information security policy (Farooq et al 2015;Chua et al 2018;Öğütçü, Testik and Chouseinoglou 2016). These studies indicated that respondents with higher educational levels had better knowledge and awareness of information security policies than those with a lower educational level.…”
Section: Importance Of Education and Training On Cdpmentioning
confidence: 92%
“…Farooq, et al [8] studied 1280 participants in six different colleges throughout India, Malaysia, Nepal, Pakistan, and Thailand. They documented Internet use and its correlation to the student user susceptibility level.…”
Section: Previous Workmentioning
confidence: 99%
“…They concluded that gender provides an insight on how a student learns cybersecurity skills. Men tend to gain security knowledge through self-taught means, while women tend to prefer formal training and interacting in their social circles [8].…”
Section: Previous Workmentioning
confidence: 99%